Effects of acute hypoxia at rest exposure on time trial performance of national category cyclists - Torres-Pérez, J.; Pinedo-Jauregi, A.; Cámara, J.; Yanci, J (Journal of Science and Cycling, 2023)
The aim of this study was to analyze the effects of rest exposure to hypoxia at performance on a simulated cycling time trial (TT) in normoxia cycling. Nine cyclists of national class participated in the study. A single blind, cross-over randomised study in which participants performed two test sessions on two different days in the laboratory was conducted. First, they were exposed to normobaric hypoxia simulating an altitude of 4500 m above sea level (FiO2=0.09) or normoxia for 30 min. After hypoxia or normoxia exposure, participants performed a 20-min simulated TT. Mechanical performance variables, perceived exertion and economy and gross efficiency (GE) amongs other physiological variables were measured. The results showed that hypoxia exposure did not provoke any changes neither in physiological variables, mechanical performance variables and perception of effort (p > 0.05, ES = -0.03 - -0.25, trivial to small), nor in economy and GE (p > 0.05, ES = 0.450, small, -0.139, trivial, respectively). The results suggest that a 30-min rest hypoxia exposure does not affect performance in a 20-min simulated TT in a cycle ergometer under normoxic conditions.